EVALUATION OF PLASMID-MEDIATED QUINOLONE RESISTANCE ASSOCIATED WITH THE QNR GENES IN CLINICAL ISOLATES OF SHIGELLA SPP. IN BAGHDAD (Iraqi Journal of Medical Sciences, 2016)
Background:Although quinolone resistance results mostly from chromosomal mutations in Enterobacteriaceae, it may also be mediated by plasmid-encoded qnr determinants. Shigella harboring the novel qnr plasmid-mediated mechanism of quinolone resistance has been described worldwide.Objective:To understand the distribution of serogroup of Shigella spp, as well as antimicrobial susceptibility and to investigate the plasmid mediated quinolone-resistant qnr genes in clinical isolates of Shigella spp. resistant to quinolone.Methods: Fifty nine clinical isolates of Shigella spp. were collected from two hospitals in Baghdad. Antimicrobial susceptibility tests were performed using disk diffusion test and minimum inhibitory concentration. The isolates were screened for the plasmid-mediated qnr genes of qnrA, qnrB, and qnrS by Multiplex polymerase chain reaction.Results:The isolation rate of Shigella spp. was 14% and observed to be high among children < 10 years and low in teenagers and adults. The highest percentage was Sh. flexneri (54.2%) followed by Sh. sonnei (37.3%) then Sh. dysenteriae (8.5%), while no Sh. boydii was found in this study. Antimicrobial susceptibility tests revealed that 54.23% and 49.2% of both Sh. flexneri and Sh. sonnei were resistant to nalidixic acid and ciprofloxacin, respectively, while Sh. dysenteriae isolates were fully susceptible to these antibiotics. The minimum inhibitory concentration value of resistant isolates of Sh. flexneri and Sh. sonnei ranged between 2-64 ?g/ml and 32-512 ?g/ml for ciprofloxacin and nalidixic acid, respectively. Multiplex polymerase chain reaction amplification of plasmid-borne qnrA, qnrB, qnrS genes revealed that the overall percentage of qnr-genes were (52.9%) distributed as (29.4%) qnrA, (20.6%) qnrS and (2.94%) qnrB detected alone or in combination. The genes were identified in (44.1%, 15/34) of quinolone resistance Shigella isolates.Conclusion:To our knowledge, this is the first report detected fluoroquinolone resistance due to the qnr gene among Shigella isolates in Iraq which is indicated that plasmid-mediated quinolone resistance has emerged in Iraqi pediatric patients.Keywords:Drug resistance, Shigella spp., Plasmid; Quinolone, qnr
Keywords: Drug resistance; Shigella spp; Plasmid Quinolone; qnr